THE WIFE’S FORGIVENESS TOWARD HUSBAND’S INFIDELITY - Erika Miftakhu Sa'adah; Hastaning Sakti; Dian Veronika Sakti (Faculty of Psychology, Diponegoro University, 2012)
The feelings of anger, hurt, disappointed, sadness felt by wifes who had husbands infidelity. Infidelity is a wrong thing but it does not mean that wife can not forgive it. The purpose of this study is to understand the process of wives forgiveness whose her husbands have affair, the factors that led to forgiveness, and benefit of forgiveness after they do it. The method that used in this study is qualitative with a phenomenological approach through snowball sampling technique.Participants consisted of three wifes whose have experienced infidelity of their husband in her marriage, has been or is in the process forgiving their husband. Interviews and observation is used to get informations, while the recording of the interview using field notes.The results found that participants performed forgiveness is a process that moves back and forth even repetitive. This process occurs under the influence of factors driving and inhibiting the occurrence of forgiveness. Husband apologizes, family supports and their cares of children help wife carry out the process of forgiveness. Forgiveness made by the participants provide benefits in the areas of physical health, mental, relational and spiritual.